Utility of serological screening for measles, mumps and rubella in immunocompromised patients - L Sticchi; M. Astengo; I.G. Iavarone; G. Icardi (Taylor & Francis Group, 2019)
Marchi et al. in their article (Measles in pregnancy: a threat for Italian women? Hum Vaccin Immunother. 2019 Jun 20:1-3) observed that 96.9% of pregnant women were positive for anti-measles IgG (with a higher risk of contracting measles in those aged 19-29 years) emphasizing the importance of serological screening before pregnancy. We evaluated seroprotection/seropositivity rates to Measles, Mumps and Rubella in 324 adults with an acquired immune-deficiency needing an immunization program. We found that younger patients (20-29 years) had a seroprevalence below 85%. Overall, a relevant proportion (21.6%, 54/250) of patients was susceptible to at least one infection needing immunization. Our results confirm the usefulness of proper strategies for identifying individuals susceptible to vaccine-preventable infections and protecting them through vaccination.